1987
DOI: 10.1136/ard.46.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with joint mobility in an adolescent population.

Abstract: SUMMARY Fixed torque devices were used to measure joint mobility at three sites in 364 adolescents including 39 families with at least two siblings. Increasing age and being male were associated with reduced laxity, and a strong effect of family was observed in the 39 sibling sets studied. The population included 47 Asians whose mobility was similar to that of the non-Asians, though the female/male difference was apparently greater in the former group. None of the above conclusions apply to index finger hypere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…All group differences were additionally adjusted for age, gender, body height, and weight, as these are determinants for blood pressure, joint mobility, skin extensibility, and quantitative ultrasound measurements. 23,24,28,29 As shown in the fourth column of Table 2, this adjustment had only a marginal influence on the results. We further assessed whether findings concerning urinary excretion of collagen degradation products might explain group differences in other clinical characteristics.…”
Section: Resultsmentioning
confidence: 91%
“…All group differences were additionally adjusted for age, gender, body height, and weight, as these are determinants for blood pressure, joint mobility, skin extensibility, and quantitative ultrasound measurements. 23,24,28,29 As shown in the fourth column of Table 2, this adjustment had only a marginal influence on the results. We further assessed whether findings concerning urinary excretion of collagen degradation products might explain group differences in other clinical characteristics.…”
Section: Resultsmentioning
confidence: 91%
“…Several studies have shown that hypermobility can either be inherited and/or acquired (Child, 1986;Klemp & Chalton, 1989). Gender, age, ethnic background and hormonal influences are factors suggested to have an impact on the degree of joint mobility (Beighton et al, 1973;Al-Rawi et al, 1985;Silman et al, 1987;Bulbena et al, 1992;Larsson et al, 1993). Carter and Wilkinson (1964) designed a score evaluating general joint laxity of five joints, and this was modified later in Beighton et al (1973).…”
mentioning
confidence: 99%
“…Gender, age and ethnic background are the three of the most discussed factors that might have an impact on the degree of joint mobility. Hormonal factors have also been discussed, since earlier studies found that females tended to be more lax than males (5)(6)(7)(8)(9) and that the degree of laxity decreased with age (5,(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%